Evolutionary ecology of beta‐lactam gene clusters in animals. Issue 12 (12th April 2017) - Suring, Wouter; Meusemann, Karen; Blanke, Alexander; Mariën, Janine; Schol, Tim; Agamennone, Valeria; Faddeeva‐Vakhrusheva, Anna; Berg, Matty P.; ,; Brouwer, Abraham; van Straalen, Nico M.; Roelofs, Dick
Abstract: Beta‐lactam biosynthesis was thought to occur only in fungi and bacteria, but we recently reported the presence of isopenicillin N synthase in a soil‐dwelling animal, Folsomia candida . However, it has remained unclear whether this gene is part of a larger beta‐lactam biosynthesis pathway and how widespread the occurrence of penicillin biosynthesis is among animals. Here, we analysed the distribution of beta‐lactam biosynthesis genes throughout the animal kingdom and identified a beta‐lactam gene cluster in the genome of F. candida (Collembola), consisting of isopenicillin N synthase ( IPNS ), δ‐(L‐α‐aminoadipoyl)‐L‐cysteinyl‐D‐valine synthetase ( ACVS ), and two cephamycin C genes ( cmcI and cmcJ ) on a genomic scaffold of 0.76 Mb. All genes are transcriptionally active and are inducible by stress (heat shock). A beta‐lactam compound was detected in vivo using an ELISA beta‐lactam assay. The gene cluster also contains an ABC transporter which is coregulated with IPNS and ACVS after heat shock. Furthermore, we show that different combinations of beta‐lactam biosynthesis genes are present in over 60% of springtail families, but they are absent from genome‐ and transcript libraries of other animals including close relatives of springtails (Protura, Diplura and insects). The presence of beta‐lactam genes is strongly correlated with an euedaphic (soil‐living) lifestyle. Beta‐lactam genes IPNS and ACVS each form a phylogenetic clade in between bacteria and fungi, while cmcI and cmcJ genes cluster within bacteria. This suggests a single horizontal gene transfer event most probably from a bacterial host, followed by differential loss in more recently evolving species.